2016
DOI: 10.18275/fire201603021076
|View full text |Cite
|
Sign up to set email alerts
|

Private Education in the Absence of a Public Option: The Cases of the United Arab Emirates and Qatar

Abstract: In the face of rising demand for private schooling in the United Arab Emirates (UAE) and Qatar, a lack of affordable schooling options, monopolistic behavior of private education providers, and unpredictable government regulations have created a complex and unequal education sector. This research employs a mixed methods comparative approach to explore the ways in which private education providers navigate the regulatory schooling environments and assess the impact on education stakeholders in the UAE and Qatar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…based private education forms part of a thinned-down neoliberal social contract, where employment-based visa sponsorship and minimal taxation come with reduced rights compared to those held by Emirati nationals, such as public subsidies and irrevocable tenure (Ali, 2010;Ridge et al, 2018). This social contract is experienced by all noncitizen communities in the UAE, albeit to differing degrees, and therefore constitutes a form of diaspora governance, shaping who migrates to the UAE and how various diasporic identities form around the noncitizen experience.…”
Section: South Asian Diaspora In the United Arab Emiratesmentioning
confidence: 99%
“…based private education forms part of a thinned-down neoliberal social contract, where employment-based visa sponsorship and minimal taxation come with reduced rights compared to those held by Emirati nationals, such as public subsidies and irrevocable tenure (Ali, 2010;Ridge et al, 2018). This social contract is experienced by all noncitizen communities in the UAE, albeit to differing degrees, and therefore constitutes a form of diaspora governance, shaping who migrates to the UAE and how various diasporic identities form around the noncitizen experience.…”
Section: South Asian Diaspora In the United Arab Emiratesmentioning
confidence: 99%
“…One study in the UAE found that a greater percentage of teachers in non-profit schools held official teaching certificates or licenses when compared to teachers in forprofit schools (94% versus 85%) (Ridge et al, 2016). The same study also found that teachers at non-profit schools had salaries 1.5 to 2 times higher than for-profit school teachers, while also receiving better benefits and having a smaller number of students per class.…”
Section: Financingmentioning
confidence: 97%
“…Non-profit schools currently comprise less than 25% of all private schools. However, these schools have been found to hire more qualified teachers and provide better benefits to their stakeholders, which include teachers and students' families alike (Ridge et al, 2016).…”
Section: Financingmentioning
confidence: 99%
See 1 more Smart Citation
“…The for-profit international education sector is increasing worldwide. Education businesses in the UAE have become more profitable as they open new schools and diversify their offerings (Ridge et al, 2015). The International Schools Research Group has tracked the growth of international schooling noting a change from 2,584 schools in 2000 to 11,616 in 2020 and income from fees of $4.9 billion in 2000 up to $54.0 billion in 2020 (ISC Research, 2020).…”
Section: Introductionmentioning
confidence: 99%